Organizational climate assessment possibilities in business organizations - Rekašiūtė-Balsienė, Rita (Psichologija, 2005)
Organizational climate has been widely discussed in the literature since the concept of social climate was proposed. They perceived organizational climate as a set of properties of the working environment which can be measured. In the article we present three set of theories of organizational climate concepts, which were found in the literature.The wide spectrum of organizational climate and performance surveys suggests that there are relationship between the climate dimensions and all kind of organizational performance indicators. It is suggested, that for a plan of activities for improving effectiveness of all organization may be used climate surveys.The purpose of this survey is to evaluate organizational climate is Lithuanian business organizations using the questionnaire which was created by the author of the article.Sample: 6 Lithuanian organizations from the service business sector, total of 591 employees. All organizations are among the firs seventh leaders of their practice field.Method: Organizational climate questionnaire (constructed by author of the article) was used in this survey. Factorial analysis distinguishes eight factors (scales): evaluations of employee attempts and performance; interrelations and respect; flexibility and quality of organization performance; employee struggle; goals knowledge; organization magnitude; cooperation; work organization. The research has been carried out in 2003–2004.Results of this survey shows, that all organizations have common peculiarities of organizational climate. Perceived as the best organizational climate aspects are organization magnitude, employee struggle, interrelations and respect; perceived as the worst organizational climate aspects are evaluation of employee attempts and performance and work organization. There was found significant differences in perceived organization conditions between managers and employees and between business departments and business support departments, what request more in depth survey. Organizational climate of two organizations are described in detail. It is suggested, that created questionnaire can be used to asses organizational climate and be useful tool for the organizational development practitioner and researcher. Practical implications and suggestions for future research are proposed.
Keywords: organizational climate; assessment